Neraca Air di Pulau Bali - Purnama, Setyawan (Forum Geografi, 2009)
As a main destination of tourism in Indonesia, Bali develops rapidly. The impact of this phenomena is the increasing of water need in some sectors, whereas the available of water is constant. There are two objectives of this research. First, to calculate water available and water need in the research area, and second to analysis the water balance. Water available cover groundwater, rivers water and springs water, whereas water need cover domestic usage, industrial and hotel usage, cattle, fishery and irrigation. Groundwater is estimated by water balance concept, river water and spring data is collected from BPSDA Bali Province, whereas the water need is counted base on secondary data that collected from some departments in Bali Province. As a result, show that the water available in Bali Island is 2.604.483.300 m³/year, which consist of groundwater 693.296.200 m³/year, rivers water 1.903.678.000 m³/year and springs 7.509.600 m³/year. The water needs reach 1.213.625.300 m³/year, which consist of domestic usage 121.276.260 m³/year, industrial and hotel usage 20.038.068 m³/year, cattle 31.272.435 m³/year, fishery 125.305.574 m³/year and irrigation 915.733.000 m³/year. Base on the water balance ratio, it is known that the number of ratio is 47% that it means almost in critical point.